Peoples, principles, and finality - Barber, NW (Oxford University Press, 2021)
The Principles of Constitutionalism examines the principles which speak to the construction and interaction of state institutions. This article responds to some criticisms of that book, in particular, those which question the universalizability of the principles, the relationship between state institutions and the people of the state, the place of democracy within constitutionalism, and the role of finality in state decision-making. It is argued that it is the link between the people and institutions, mediated by democracy, that both explains and justifies the state’s claim to act as the final arbiter of the obligations of its people.